PENGAPLIKASIAN TEKNIK ENGINEERED PRINT DENGAN KONSEP ZERO WASTE FASHION DESIGN PADA POLA BUSANA DIGITAL READY TO WEAR WANITA - Nadhillah Tenrioja Mulyadi (Universitas Ciputra Surabaya, 2022)
Ready-to-wear clothing is the most common type of clothing that is categorized with a massive, fast production process and the affordable prices tendencies in order to fulfill the human clothing needs. Due to the massive and fast production process, the fashion industry has an adverse effect for the environment because of its inefficiency to generate the fabric waste which is more than 15%. There are two types of fabric waste, production waste that carried out by the industry and post-production waste generated by consumers. One of the efforts in optimizing fabrics is using the zero waste fashion design method by utilizing technology. Engineered print is one surface techniques by adjusting the motifs on clothing patterns using computer software to produce clothing that gives the illusion of a shape that is not interrupted by stitches.The engineered print technique with the concept of zero waste fashion design has the potential to be more effective in reducing fabric residue in the production process by at least 15 percent. Based on the previous statement, this research is conducted to producing women's ready to wear clothing with the concept of zero waste fashion design and to explain how the production process of clothing using engineered print techniques with zero waste fashion design. The methodology in this study uses qualitative methods in the form of literature studies, indirect observations, exploration of clothing patterns based on the concept of zero waste fashion design, and Rafflesia arnoldii stylization for engineered print motifs as a surface technique. Keywords: zero waste fashion design, engineered print, ready-to-wear.